ANALISIS PENGARUH HUMAN CAPITAL TERHADAP KEMISKINAN DI PULAU JAWA TAHUN 2017 – 2021 - Abdillah Qurais, Salman Alfarsi (Journal of Development Economic and Social Studies, 2023)
This study aims to analyze the relationship between Human Capital and Poverty in Java. This study uses a quantitative approach with the Panel Data Regression method which analyzes the relationship between variables, using panel data. The sample used in this study totaled 565 data from 113 cities/regencies on Java Island in 2017-2021 sourced from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK). The results of this study indicate that the variables Human Development Index, Open Unemployment Rate, Economic Growth, and Capital Expenditures have a significant effect on Poverty in Java Island. It is hoped that this research can help provincial, city/regency governments in Java in making policies, especially in alleviating regional poverty which is still centered on Java Island in terms of human capital development through the Human Development Index (HDI), unemployment, economic growth, and government capital expenditure.